All That Glitters Is Not Gold: The Penalty Effect of Conspicuous Consumption in Services and How It Changes With Customers and Contexts. (November 2018) - Mende, Martin; Scott, Maura L.; Bolton, Lisa E.
A service provider's conspicuous consumption can undermine customer attitudes and behavioral intentions toward the provider—a so-called penalty effect of conspicuous consumption . Four studies investigate customer and contextual factors that moderate this penalty effect. The results show that customers low in materialism penalize service providers who consume conspicuously (e.g., decreased patronage intentions). In addition, as another facet of the penalty effect, a service provider's conspicuous consumption undermines customer cost-benefit assessments (decreased perceived value and price fairness), which function as mediating variables. However, service providers can use "service warmth" as a protective strategy to attenuate the penalty effect. Notably, materialistic customers do not react more favorably to service providers who engage in conspicuous consumption (in contrast with their established tendency to favor conspicuous goods). Taken together, the results provide a deeper and theoretically nuanced understanding of when and how customers respond negatively to conspicuous service providers, with meaningful implications for the management of services. For example, when service firms design their aesthetic labor strategy, they should consider their customers' levels of materialism accordingly. In addition, service firms need to educate their frontline employees about the potential downsides of displaying conspicuous consumption cues.